2016
DOI: 10.1021/acsami.6b09370
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Timed Release Properties of Self-Rupturing Gels

Abstract: Swelling of polymeric hydrogels is sensitive to their cross-link densities. Here, we exploit this principle to prepare self-rupturing gels which are based on a commonly-used, nontoxic, and inexpensive polyelectrolyte, poly(acrylic acid), and are prepared through a simple and low-cost polymerization-based technique. The self-rupture of these covalently cross-linked gels is achieved by preparing them to have highly nonuniform cross-link densities. This heterogeneity in cross-linking leads to highly nonuniform sw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 73 publications
0
8
0
Order By: Relevance
“…(B) Nonuniform swelling of regions of different cross-link densities results in complete rupture at the interface. (Reprinted with permission from ref . Copyright 2016 American Chemical Society.)…”
Section: Swelling-induced Mechanochemical Activation In Multidimensio...mentioning
confidence: 99%
“…(B) Nonuniform swelling of regions of different cross-link densities results in complete rupture at the interface. (Reprinted with permission from ref . Copyright 2016 American Chemical Society.)…”
Section: Swelling-induced Mechanochemical Activation In Multidimensio...mentioning
confidence: 99%
“…This was shown to be a reasonable assumption for polyacrylamide gels in water having spherical shapes. 8 However, later studies observed phenomena such as surface instabilities 31 and self-rupturing 9 in response to swelling. Therefore, the assumption of internal stresses approaching zero and the appropriateness of theoretical regimes to account for geometrical constraints, mechanical loads, and non-idealities or heterogeneity associated with polymer networks used in practice has come into question.…”
Section: Introductionmentioning
confidence: 99%
“…While the research literature is rich with examples of biomaterials developed from PEG, 2,[4][5][6][7] there are still challenges associated with this platform: there remains a need to better understand the physical behavior and transient dynamics associated with swelling and how it contributes to observed phenomena such as surface instabilities and rupturing. [8][9][10][11][12][13][14] To address these limitations, here we employ high-speed imaging of rupture events during hydrogel swelling to determine what factors lead to catastrophic failure.…”
Section: Introductionmentioning
confidence: 99%
“…While the research literature is rich with examples of biomaterials developed from PEG, [2,[4][5][6][7] there are still challenges associated with this platform: there remains a need to better understand the physical behavior and transient dynamics associated with swelling and how it contributes to observed phenomena such as surface instabilities and rupturing. [8][9][10][11][12][13][14] To address these limitations, here we employ high-speed imaging of rupture events during hydrogel swelling to determine what factors lead to catastrophic failure.…”
Section: Introductionmentioning
confidence: 99%
“…This was shown to be a reasonable assumption for polyacrylamide gels in water having spherical shapes. [8] However, since this analysis more recent studies have revealed surface instabilities [28] and self-rupturing [9] behavior in response to swelling, and thus the appropriateness of these theoretical regimes to account for geometrical constraints, mechanical loads, and non-idealities or heterogeneity associated with polymer networks used in practice has come into question. [29] Phenomena such as in situ surface structuring and self-rupturing are interesting and relevant for interfacial design and drug delivery applications.…”
Section: Introductionmentioning
confidence: 99%